1995
DOI: 10.1002/1097-0142(19951201)76:11<2351::aid-cncr2820761125>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequent expression of P-glycoprotein/MDR1 by nasal T-cell lymphoma cells

Abstract: Background. Lethal midline granuloma is now considered to be a malignant lymphoma derived from peripheral T cells or from natural killer cells. The therapeutic outcome of nasal T‐cell lymphoma (NL) treated by conventional chemotherapy for non‐Hodgkin's lymphoma is poor, although some patients have a good response to radiotherapy. To clarify the mechanisms of drug resistance, the expression of P‐glycoprotein (P‐gp)/MDR1, which is the product of the multidrug resistance (MDR) 1 gene, and MDR3 mRNA in NL cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(187 citation statements)
references
References 25 publications
7
177
0
3
Order By: Relevance
“…P-gp was found to be overexpressed in various types of hematological malignancies including extranodal NK/T-cell lymphoma, nasal type. Previous series identified the immunohistochemical expression of P-gp from 54 to 90% in extranodal NK/T-cell lymphoma, nasal type [15,19,20]. In our study, a high expression rate of P-gp (67%) in previously untreated patients was confirmed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…P-gp was found to be overexpressed in various types of hematological malignancies including extranodal NK/T-cell lymphoma, nasal type. Previous series identified the immunohistochemical expression of P-gp from 54 to 90% in extranodal NK/T-cell lymphoma, nasal type [15,19,20]. In our study, a high expression rate of P-gp (67%) in previously untreated patients was confirmed.…”
Section: Discussionsupporting
confidence: 82%
“…P-gp was found to be overexpressed in various hematological malignancies including NHL [13]. Multiple investigators detected highlevel expression of P-gp in normal or abnormal NK cells using different methods [14][15][16][17]. Nevertheless, convincing clinical data about correlation between P-gp expression and chemoresistance or prognosis is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The ENKL tumor cells express the multidrug resistance (MDR) 1/ABCB1 gene and its product, P-glycoprotein [32][33][34]. This observation is thought to be the major reason why ENKL is resistant to CHOP or CHOP-like chemotherapies, which are comprised mainly of MDR-related agents.…”
Section: Prospective Clinical Trials For Newly Diagnosed Localized Namentioning
confidence: 99%
“…These involve mutations of genes regulating apoptosis such as Fas and p53, [6][7][8][9][10] as well as expression of P-glycoproteins. 11 Moreover, a low expression level of the granzyme B protease inhibitor 9 was associated with a worse prognosis and cell dedifferentiation, suggesting a role for this protein in the pathophysiology of these malignancies. 5 However, the mechanisms involved in the pathogenesis and resistance to treatment still remain poorly understood, and the deep research for this special tumor has been hampered by its rarity and insufficient supply of the tumoral samples.…”
Section: Introductionmentioning
confidence: 99%